PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN MARKETING BANK SYARIAH - Amianti, Ita; ., Supriyanto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
Based on the analysis of research, known as follows: employee motivation at PT. BPRS Bekasi City Administration has an average value of 71,6, with the highest and lowest values 54 87. Employee performance PT. BPRS Bekasi City Administration has an average value of 63,6, with the highest 76 and lowest values 52. From the simple regression test the influence of motivation as a variable X to the employee's performance as a variable Y. That the correlation between the motivation of the employee's performance of R = 0.925 including the category of very strong relationship. The coefficient of determination of 0,856 which means that motivation affects employee performance by 85.6% while 14.4% influenced by other factors. And the results of the regression equation is Y = 8,874 + 0,883 X, meaning that the value 8,874 is a constant value of ? is shown that if the motivation variables remain constant, or the employee's performance of 8,874. If the variables of motivation to increase one unit, then the employee's performance increased by 0,883. So this is the conclusion of this research there is a correlation between the motivations with the employee's performance at PT. BPRS Bekasi City Government